Attendance Mobile Application With Face Recognition and Detect Location - Andika Bayu Hasta Yanto; Ahmad Fauzi; Novita Indriyani (Universitas Islam Kuantan Singingi, 2022)
Every company must have an attendance policy for each of its employees for the purpose of employee attendance and performance reports in the performance of their work, but currently there are still many companies that still have an absence system that is not computerized, so the calculation and accounting process is still done manually, because everything is calculated manually, it is possible that there are errors in the calculations and take time to process data absence of all employees. Therefore, an application that can automatically process and record data is needed to avoid errors and speed up the data processing process. In addition, the application can facilitate employees' attendance as it can be accessed directly from cell phones by using facial recognition and location detection to prove the attendance of employees.